PENGARUH PERBANDINGAN JUMLAH STARTER TERHADAP PROSES FERMENTASI WINE APEL MENGGUNAKAN NOPKOR MZ-11 - Rini Kusumawati; Muhammad Adi Irawan; Aprilina Purbasari (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Based on Department of Agriculture and Forestry Batu, Malang, in the 2010, the number of apple productions are 2,574,852 trees with productivity reaching 17 kg / tree. From all of trees only 60-70% of apples that can be harvested and sold in the market. The apple that doesn’t sell in the market, named reject apple. Until now, this apple could not be fully utilized. NOPKOR MZ 11 is multicultural is the main constituent microbes with S. Cerevicea Bolognesis that can convert sugar to alcohol, such as others S. Cerevicea. The advantages of this NOPKOR is its durability very high so it does not die easily. The main objective from this research is to determine the effect of the starter substrate ratio the growth of biomass and the resulting alcohol. The method which used are starter that added and the time of fermentation. And then from the data of refractive index result the phenomena of fermentation process. From the refractive index and using a standard curve, the data is converted. So that the refractive index is known and the amount of biomass levels of alcohol contained in the wine. Based on the research results, alcohol and optimal growth obtained in the ratio of 10% starter volume, it can able because a balanced amount of nutrients obtained by microbes thus more optimal growth and the amount of alcohol that produced is also higher. The longer of fermentation time, the amount of alcohol obtained and the number of microbes continued to increase, until the end of fermentation the increase was not too rapidly and tends to approach a constant, this is because the microbes have entered the stationary phase so that growth is not as fast as the previous phase.